Regulatory Non-Coding RNAs in Familial Hypercholesterolemia, Theranostic Applications - Keshavarz Alikhani, Hani; Pourhamzeh, Mahsa; Seydi, Homeyra; Shokoohian, Bahare; Hossein-khannazer, Nikoo; Jamshidi-adegani, Fatemeh; Al-Hashmi, Sulaiman; Hassan, Moustapha; Vosough, Massoud (Frontiers in Cell and Developmental Biology, 2022)
Familial hypercholesterolemia (FH) is a common monogenic disease which is associated with high serum levels of low-density lipoprotein cholesterol (LDL-C) and leads to atherosclerosis and cardiovascular disease (CVD). Early diagnosis and effective treatment strategy can significantly improve prognosis. Recently, non-coding RNAs (ncRNAs) have emerged as novel biomarkers for the diagnosis and innovative targets for therapeutics. Non-coding RNAs have essential roles in the regulation of LDL-C homeostasis, suggesting that manipulation and regulating ncRNAs could be a promising theranostic approach to ameliorate clinical complications of FH, particularly cardiovascular disease. In this review, we briefly discussed the mechanisms and pathophysiology of FH and novel therapeutic strategies for the treatment of FH. Moreover, the theranostic effects of different non-coding RNAs for the treatment and diagnosis of FH were highlighted. Finally, the advantages and disadvantages of ncRNA-based therapies vs. conventional therapies were discussed.